Multilevel transmission scheme for wireless broadcasting system - SUN Xiang-tao1; GONG Ke2 (Tongxin xuebao)
A multilevel transmission scheme was developed to take full advantage of the transmission channel capacity and meet the requirements of different users and different types of receiving equipments.In this scheme,broadcasting datas were divided into different levels of error protection and transmission rate by using multilevel coding and multi-resolution modulation techniques.Multistage decoder was adopted,which allowed user to receive data at different rate according to its transmission channel quality or its receiver ability.Simulation results show this scheme has good performance over both AWGN channel and multipath channel.